Perbedaan Penyuluhan Dengan Media Video dan Media Power Point Presentation Terhadap Pengetahuan dan Sikap Tentang Sayur dan Buah Pada Siswa di SD Negeri 12 Kesiman dan SD Negeri 7 Kesiman - Ambartana, I Wayan; Widya Astuti, Ni Wayan; Suiraoka, I Putu (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
One message of balanced nutrition is to increase consumption of vegetables and fruit. Low consumption of vegetables and fruit can cause nutritional problems in school children. The reason is that children's eating behavior is unstable and there are many instant foods that contain little vegetables and fruit. Another cause is the lack of knowledge about consumption of vegetables and fruit. One way to achieve this is through counseling. Media is needed to achieve success, the available media include video media and power point. The purpose of this study was to determine the differences in knowledge and attitudes of students at Elementary School of 12 Kesiman and Elementary School of 7 Kesiman about vegetables and fruit using video and media.power point. This type of research is a quasi-experimental with a plan The Matching Only Pretest-Posttest Control Group Design and using only the two-group average independent which totaled 72 people. Data was collected by filling out a questionnaire. Data is presented in frequency and cross tables. Test results Mann-Whitney showed that there was a significant difference in knowledge data between students of Elementary School of 12 Kesiman and Elementary School of 7 Kesiman (p-value = 0.005). The same attitude test was carried out, which resulted in a significant difference in attitude between students of Elementary School of 12 Kesiman and Elementary School of 7 Kesiman (p-value = 0.013). Suggestions that can be done is to consider the use of video and media media power point as one of the student learning methods.